ANALISIS KOMPARATIF PREDIKSI KEBANGKRUTAN DENGANMODEL OHLSON, SPRINGATE, ZMIJEWSKI, DAN GROVER PADA PERUSAHAAN KONSTRUKSI DAN BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rachaprima, Muhammad Reza; Tanjung, Amries Rusli; Idrus, Rahmiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study purpose to determine the bankrupcty prediction model is most suitable for use in its application to construction and building companies in Indonesia, by comparing four financial distress prediction model, the model of Ohlson, Springate, Zmijewski and Grover. Comparisons were made by analyzing the accuracy of each model. The data used in the form of annual financial statements published by the company on the Indonesian Stock Exchange website. The sample used is a construction and building company in Indonesia listed on the Stock Exchange during the years 2009-2013. The sampling technique is purposive sampling with a total sample obtained by 5 companies. The results showed that the most accurate model is the model Springate, Zmijewski, and Grover with accuracy level 100%.Keywords: Bankruptcy, Predictions Models, and Financial Ratio.